Investigation in Vocation High School for Attitude and Motivation Students in Learning Physics Subject - Tanti Tanti; Wiji Utami; Deliza Deliza; Mojtaba Jahanifar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates the relationship between students’ attitudes and their motivation to study physics in vocational high schools. Recognizing that physics is often perceived as a difficult subject, this research seeks to understand how affective factors influence student engagement and achievement, particularly in vocational education settings where applied sciences are critical. Methodology: The study employs a quantitative descriptive design with a correlational approach, using validated questionnaires distributed to vocational students. To enrich the quantitative findings, semi-structured interviews were conducted to explore students' perceptions more deeply based on specific indicators of attitude and motivation. Data were analyzed using both descriptive and inferential statistics, particularly Pearson correlation analysis. Main Findings: The results revealed that both students’ attitudes towards physics and their motivation to learn were generally in the “fairly good” category. A positive and significant correlation between the two variables was found, with a moderate Pearson correlation coefficient of 0.622, indicating that students with a more positive attitude tend to have higher motivation levels. This emphasizes the vital role of affective domains in supporting physics learning outcomes. Novelty/Originality of this study: This study introduces a novel integrated analytical framework that merges quantitative correlation data with qualitative insights, providing a deeper understanding of the synergy between attitudes and motivation. Unlike previous research that often examined these factors independently, this study emphasizes their interrelated impact on vocational physics education, offering new directions for designing affective-based learning interventions aimed at improving student cognitive, affective, and psychomotor performance in technical fields.